2021
DOI: 10.1039/d1qi00128k
|View full text |Cite
|
Sign up to set email alerts
|

An albumin-binding Gd-HPDO3A contrast agent for improved intravascular retention

Abstract: Gadolinium contrast agents that bind to human serum albumin (HSA) can achieve significantly higher relaxivity values and show improved vascular retention time. Most contrast agents of this design are linear...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Furthermore, because both Gd chelates have the same ethoxybenzyl moiety, the higher percent HSA binding value suggests that additional electrostatic interactions were induced by partially charged protein residues and pendant arms rather than hydrophobic interactions. Several studies have found that negative Gd chelates have a similar enhanced binding effect on HSA. In order to gain a better understanding of the HSA interaction, we measured the relaxivity change in several anionic media and HSA solutions in subsequent sections.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, because both Gd chelates have the same ethoxybenzyl moiety, the higher percent HSA binding value suggests that additional electrostatic interactions were induced by partially charged protein residues and pendant arms rather than hydrophobic interactions. Several studies have found that negative Gd chelates have a similar enhanced binding effect on HSA. In order to gain a better understanding of the HSA interaction, we measured the relaxivity change in several anionic media and HSA solutions in subsequent sections.…”
Section: Resultsmentioning
confidence: 99%
“…Contrast agents (CAs) play a crucial role in diagnostic magnetic resonance imaging (MRI) as they add relevant physiological information to the outstanding anatomical resolution of the images acquired with this modality. They usually consist of paramagnetic gadolinium complexes that cause a marked reduction in the proton relaxation times in the regions where they distribute. Their efficiency is first of all represented by their relaxivity ( r 1 ), i.e., the relaxation enhancement brought to solvent water protons at a concentration of 1 mM. , Over the years, probe developers have paid great attention to improving the relaxivity of gadolinium-based contrast agents (GBCAs), , in particular, by optimizing their structures in terms of the number and exchange rate of the coordinated water molecules in the inner and in the second coordination sphere and by controlling the molecular reorientational time through the introduction of substituents on the surface of the ligand capable of either increasing their molecular weight (MW) or setting up suitable interactions with macromolecules. , Often, the target macromolecule is represented by human serum albumin (HSA) , thus endowing the GBCA with blood pool properties, with a primary aim of application in the field of the acquisition of angiographic images. In most cases, the binding to HSA has been pursued through the introduction of substituents capable of recognizinng the well-known binding sites for lipophilic drugs usually identified as the Sudlow sites. , …”
Section: Introductionmentioning
confidence: 99%